Towards a mechanically stable polymer electrolyte for Li-ion batteries - Jenssen, Kristoffer (Nanyang Technological University, 2022)
Structural power composites stand out as a potential solution to the current transportation system's requirement for more efficient and environmentally friendly cars. Recent research has shown that these components may be used to give high-performance composites with electrochemical properties. In this study, the improvement of mechanical strength and ionic conductivity between solid polymer electrolytes and gel polymer electrolyte will be studied. Consequently, solid polymer electrolyte and gel polymer electrolyte electrochemical and mechanical properties will be compared to elucidate their suitability as structural battery electrolyte. Of the structural electrolyte systems studied, PEEK reinforced PEO-LiTFSI gives better result as it can achieve considerably high ionic conductivity (10-4 S cm-1) while maintaining high tensile strength (100 MPa) and high young’s modulus (900 MPa).